Effects of Dilution Systems in Olfactometry on the Recovery of Typical Livestock Odorants Determined by PTR-MS - Pernille Lund Kasper; Dietmar Mannebeck; Arne Oxbøl; Jens Vinge Nygaard; Michael Jørgen Hansen; Anders Feilberg (Sensors, 2017)
The present study provides an elaborate assessment of the performance of olfactometers in terms of odorant recovery for a selection of odorants emitted from livestock houses. The study includes three different olfactometer dilution systems, which have been in use at accredited odor laboratories. They consist of: (i) a custom-built olfactometer made of glass tubes, (ii) a TO8 olfactometer, and (iii) an Olfacton dilution system based on a mass flow controller. The odorants include hydrogen sulfide, methanethiol, dimethyl sulfide, acetic acid, butanoic acid, propanoic acid, 3-methylbutanoic acid, 4-methylphenol, and trimethylamine. Furthermore, n-butanol, as the reference gas in the European standard for olfactometry, EN13725, was included. All measurements were performed in real time with proton-transfer-reaction mass spectrometry (PTR-MS). The results show that only dimethyl sulfide was almost completely recovered in all cases, while for the remaining compounds, the performance was found to vary significantly (from 0 to 100%) depending on the chemical properties of the compounds, the concentration levels, the pulse duration, and the olfactometer material. To elucidate the latter, the recovery in different locations of the TO8 olfactometer and in tubes of different materials, that is, poly-tetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), stainless steel and SilcoTek-coated steel, were tested. Significant saturation effects were observed when odorants were in contact with stainless steel.